Comparison of mechanical and morphological properties of 3-D printed functional prototypes: Multi and hybrid blended thermoplastic matrix. (May 2022) - Kumar, Sudhir; Singh, Rupinder; Singh, TP; Batish, Ajay
This article reports the comparison for mechanical and morphological properties of 3-D printed tensile specimen with fused deposition modeling by using multiblended and hybrid blended polylactic acid (PLA) matrix. The multiblended PLA matrix was 3-D printed as tensile specimen (as per American Society for Testing and Materials 638 type IV) comprising of 06 layers (01 layer PLA + 01 layer of PLA + polyvinyl chloride + 02 layers of PLA + wood powder + 02 layers of PLA + Fe3 O4 ) each with layer thickness of 0.53 mm. The hybrid blended PLA matrix was also 3-D printed with similar dimensions and printing conditions. The composition/proportion of hybrid blended and multimaterial blended matrix has been selected on the basis of similar melt flow index (MFI) range and the final matrix was compared on basis of equal number of layers (06), similar rheological range (MFI: 40–45 g/10 min) and volume of product (same dimension of prototype). The results of study suggested that the 3-D printed functional prototype of multiblended PLA matrix has better mechanical and morphological properties than hybrid blended PLA matrix. The peak strength and break strength of hybrid blend-based prototype were observed to be 29.56 MPa and 26.60 MPa, respectively, whereas for the multimaterial-based functional prototypes, it was 46.28 MPa and 41.65 MPa, respectively. The results are also supported with scanning electron microscopy-based images, 3-D rendered images, and energy-dispersive X-ray analysis analysis.